Pendidikan Tinggi Agama Islam dan Kohesi Sosial di Indonesia - Kosasih, Ojang; T, Sutaryat; Hanafiah, Hanafiah (TSAQOFAH, 2023)
After the fall of authoritarian rule, religious people in Indonesia sought to improve relations through progressive Islamic education. Experts in this field study how community Islamic education leaders work to "renew" Islamic thought. They collected data between December 2005 and March 2006. The report examines the core values of education leaders as they seek to transform the State Institute of Islamic Studies into a true university. This study uses the tradition of promoting democracy through education as its basis. It further analyzes how this tradition has served as a foundation for teachers to promote cohesion in society and address social cohesion problems.